Gestión de ganancias en el riesgo de quiebra de las empresas públicas mexicanas: Management of earnings in the risk of bankruptcy of Mexican public companies - Cumpean Luna, Joel Alejandro; Briseño García, Arturo; Arango Herrera, Eduardo (Revista de Ciencias Sociales, 2021)
A highly studied phenomenon within the business environment is bankruptcy in organizations. However, one approach with which this status has been little related is the quality of financial information reported by companies. In this way, the objective of this research is to analyze the relationship between bankruptcy risk and profit management practiced by public companies in Mexico. Analyzing a universe of 145 companies and taking as a sample a total of 86 organizations that were listed on the Mexican Stock Exchange during the 2014-2018 period, a quantitative, longitudinal, and causal study was developed, collecting information from secondary sources such as Bloomberg and reports annual companies on their websites. A panel regression of Generalized Least Squares was performed with the support of Stata 12. The results show that the increase in profit management increases the risk of bankruptcy in the companies in the sample of this study. It is concluded that, when managing the profits of the companies of the Mexican Stock Exchange, the risk of bankruptcy of the same can be increased and represent a serious problem for their stakeholders.